Eating Behaviour Predicts Weight Loss Six Months after Bariatric Surgery: A Longitudinal Study - Subramaniam, Kavitha; Low, Wah Yun; Lau, Peng Choong; Chin, Kin Fah; Chinna, Karuthan; Kosai, Nik; Taher, Mustafa; Rajan, Reynu (MDPI, 2018)
Bariatric surgery is currently the most durable weight loss solution for patients with morbid obesity. The extent of weight loss achieved, however, is subject to variation due to various factors, including patients’ behaviour. In this study, we aimed to identify pre-and post-surgical predictors of weight loss following bariatric surgery. This prospective study included 57 participants who went through bariatric surgery (laparoscopic Roux-en-Y gastric bypass: n = 30; laparoscopic sleeve gastrectomy: n = 23; one anastomosis gastric bypass-mini gastric bypass: n = 4) in two tertiary referral hospitals. Consenting participants were assessed prior to surgery (T0 ), and three months (T1 ) and six months (T2 ) after surgery. The assessment included interview and anthropometric measurements. The interview was done with the aid of instruments, including the Hospital Anxiety and Depression Scale (HADS) for anxiety and depression screening and the Dutch Eating Behaviour Questionnaire (DEBQ) for eating behaviour assessment. Baseline comorbidity status was obtained from medical records. A Generalised Estimating Equation (GEE) was developed to determine predictors of weight loss. Participants in the study were mostly women (n = 37, 65%) with a mean age of 39.4 (SD = 10.01) years. The mean excess BMI loss (EBMIL) and total weight loss (TWL) at the sixth month was 63.31% and 23.83%, respectively. Anxiety, depression, and external eating scores reduced over time. Advancing age, high BMI, and higher scores for emotional and external eating emerged as significant negative predictors for TWL%. It can be concluded that the patients experienced substantial weight loss after surgery. Continuous monitoring of psychological well-being and eating behaviour are essential for optimal weight loss.